The Relationship Between Academic Stress and Psychological Well Being of SMA Negeri 1 Pantai Cermin Students During the Covid-19 Pandemic - Bunga Islami Yusa (Inovan Publisher, 2024)
Since 2020, the world, including Indonesia, has been declared infected with a virus that is considered dangerous and has claimed many lives, namely the Covid-19 virus. In order to reduce the transmission rate, the government has issued various policies, one of which is a policy in the learning process where the learning process is limited or carried out online. However, the learning process may be carried out offline by meeting the applicable requirements. This change in the learning system is considered less effective and can trigger stress for students so that it can affect their psychological well-being. The purpose of this study is to see the relationship between academic stress and psychological well-being of students at SMA Negeri 1 Pantai Cermin during the Covid-19 pandemic. The scales used in this study are the Psychological Well-Being Scale and the Academic Stress Scale carried out by the researcher. This study was conducted on 169 subjects from SMAN 1 Pantai Cermin using the incidental sampling technique. The correlation analysis in this study used the Pearson Product moment correlation technique with the results of the correlation between academic stress and psychological well-being, namely r = -0.285 with a significance value of p = 0.000, so Ha is accepted. This means that there is a significant negative relationship between academic stress and psychological well-being in students of SMAN 1 Pantai Cermin.